Capital the eruption of Delhi - Dasgupta, Rana (The Penguin Press, 2014)
Capital is an intimate portrait of the city of Delhi which bears witness to the extraordinary transmogrification of India's capital. But it also offers a glimpse of what capitalism will become in the coming, post-Western world. The story of Delhi is a parable for where we are all headed.